Application of Classification Algorithms of Machine Learning in Practice - Israilov Sharobiddin Makhammadyusufovich (Periodica Journal, 2023)
In this article, machine learning is an important technology in the field of programming that studies data analysis and mapping data to class classes. Its main tasks are to analyze data and connect them to certain classes, to teach how to perform classification. This is classification algorithms data in analysis, technical in the fields and another in the fields wide is used
Keywords: technical; Mining; weightless sound to give Knn method; Vector characters